Short-course quinazoline drug treatments are effective in the Litomosoides sigmodontis and Brugia pahangi jird models. (April 2020) - Hübner, Marc P.; Gunderson, Emma; Vogel, Ian; Bulman, Christina A.; Lim, K.C.; Koschel, Marianne; Ehrens, Alexandra; Frohberger, Stefan J.; Fendler, Martina; Tricoche, Nancy; Voronin, Denis; Steven, Andrew; et al.
Abstract: The quinazolines CBR417 and CBR490 were previously shown to be potent anti-wolbachials that deplete Wolbachia endosymbionts of filarial nematodes and present promising pre-clinical candidates for human filarial diseases such as onchocerciasis. In the present study we tested both candidates in two models of chronic filarial infection, namely the Litomosoides sigmodontis and Brugia pahangi jird model and assessed their long-term effect on Wolbachia depletion, microfilariae counts and filarial embryogenesis 16−18 weeks after treatment initiation (wpt). Once per day (QD) oral treatment with CBR417 (50 mg/kg) for 4 days or twice per day (BID) with CBR490 (25 mg/kg) for 7 days during patent L. sigmodontis infection reduced the Wolbachia load by >99% and completely cleared peripheral microfilaremia from 10–14 wpt. Similarly, 7 days of QD treatments (40 mg/kg) with CBR417 or CBR490 cleared >99% of Wolbachia from B. pahangi and reduced peritoneal microfilariae counts by 93% in the case of CBR417 treatment. Transmission electron microscopy analysis indicated intensive damage to the B. pahangi ovaries following CBR417 treatment and in accordance filarial embryogenesis was inhibited in both models after CBR417 or CBR490 treatment. Suboptimal treatment regimens of CBR417 or CBR490 did not lead to a maintained reduction of the microfilariae and Wolbachia load. In conclusion, CBR417 or CBR490 are pre-clinical candidates for filarial diseases, which achieve long-term clearance of Wolbachia endosymbionts of filarial nematodes, inhibit filarial embryogenesis and clear microfilaremia with treatments as short as 7 days. Graphical abstract: Image 1 Highlights: CBR417 and CBR490 provide long-term effects in 2 chronic filaria jird models. CBR417 and CBR490 deplete >99% Wolbachia in B. pahangi and L. sigmodontis filariae. CBR417 and CBR490 clear L. sigmodontis microfilariae after 10–14 weeks. CBR417 and CBR490 inhibit filarial embryogenesis in both models. Suboptimal doses do not maintain reduction of microfilariae and Wolbachia .